Efinery wastewater by using hydrogen peroxide - Abdul Aziz, Mohd Azoddein; M. C., Mamat; Ahmad Bazli, Bustary (Universiti Malaysia Pahang, 2018)
Petroleum refinery plants generate effluents, solid waste and sludge composed of organic, inorganic compounds including heavy metals. Spent Caustic or used caustic soda is a wastewater generated from the scrubbing process in the petroleum refinery industry. Further treatment is needed for petroleum refinery wastewater because it typically has high concentration of sulfide which is known as the most hazardous pollutants. Spent caustic is highly corrosive due to the high pH because it typically has pH more than 12 and sulfide concentration exceeding in 2-3 wt. %. It is released to environment as dissolved sulfide (S2- and HS-) in wastewater and H2S in waste gases. Thus, the removal of sulfide from petroleum refinery wastewater that can bring harmful to human and environmental problems because of their alkalinity and high sulfide level is very important.